Silicon as a ubiquitous contaminant in graphene derivatives with significant impact on device performance - Rouhollah Jalili (Nature Portfolio, 2018)
Silicon-based contaminants are ubiquitous in natural graphite, and they are thus expected to be present in exfoliated graphene. Here, the authors show that such impurities play a non-negligible role in graphene-based devices, and use high-purity parent graphite to boost the performance of graphene sensors and supercapacitor microelectrodes.